CLAY BRICK WASTE: NEW FILLER TO NATURAL RUBBER COMPOSITE - Neves, Lucas [UNESP]; Paiva, Fábio F. G. [UNESP]; Bacarin, Giovani B. [UNESP]; Cabrera, Flávio Camargo [UNESP]; Job, Aldo E. [UNESP] (My University, 2021)
The development of urban cities increases the amount of construction and demolition waste, such as ceramic materials, mainly clay bricks, and consequently, generates cost for the management and environmental disposal due to the few routes to recycle or reuse them. Here, it is proposed a new approach to reuse clay bricks waste (CB) composed by red ceramic as reinforcement filler to natural rubber (NR) composites. It was verified that the residue is mostly composed of silicon, which is a filler widely used in rubber industry as SiO2, to mechanically reinforce composites. Tensile strength showed an increment around 16% when 20 phr of CB waste was added to the natural rubber (reaching 12,4 MPa). In addition, composites with 10 phr of waste showed great abrasion resistance and the hardness property increased as CB waste was added. The results indicate that the residue can be used as a possible filler in natural rubber products.
Keywords: clay bricks; composites; natural rubber; reuse